Cardiac function and cognitive function in patients with obstructive sleep apnea - Ensieh Vahedi (Sleep Science and Practice, 2021)
Abstract Objectives This study was designed to evaluate echocardiographic findings in patients with obstructive sleep apnea (OSA) with cognitive impairment and compare it with the control group. Methods Sixty-seven OSA patients and 52 group of healthy controls were evaluated prospectively by Mini-Mental State Examination questionnaire and trans-thoracic echocardiography. Results The cognitive impairment and diastolic dysfunction were 19.6% (P = .002) and 18.4% (P = .016) more prevalent in OSA group compared to the control group. The mean tricuspid regurgitant gradient, pulmonary artery size, and transmitral A velocity were higher, but mean right ventricular peak systolic velocity, tricuspid annular plane systolic excursion (TAPSE), fractional area change (FAC), transmitral E/A ratio, and annular E’ velocity were lower in the OSA group than the control group. Comparing the patients with and without cognitive disorders, showed significant differences regarding the size of right atrium, TAPSE and FAC (P < .05). Conclusions OSA patients need accurate cardiac examinations, early diagnosis, and interventions to prevent the progression of cardiac dysfunction, especially older male patients with higher BMI and impaired cognition. Further studies are needed to determine the exact link between the OSA, obesity, and cardiac physiology.